2009
DOI: 10.1159/000264826
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Predictors of Death 1 Month and 3 Years after First-Ever Ischemic Stroke: Data from the First National Acute Stroke Israeli Survey (NASIS 2004)

Abstract: Background: Despite declining age-adjusted stroke mortality rates, the disease remains the third most common cause of death in Israel. Based on a national survey, we examined mortality rates during the first 3 years after a first-ever acute ischemic stroke (IS) and the major predictors of short-term (1 month) and long-term (3 years) mortality. Methods: In the National Acute Stroke Israeli Survey (NASIS 2004), data were collected on all hospitalized stroke patients in Israel during a 2-month period. Mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
44
2
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 53 publications
10
44
2
5
Order By: Relevance
“…Our study also showed that heart failure may also be a predictor of the one-year mortality of patients with cerebral infarction but not of those with cerebral hemorrhage. Previous studies (Eriksson and Olsson 2001;Koton et al 2010) similarly reported that congestive heart failure is a significant predictor of mortality in stroke patients. A small number of heart-failure patients with cerebral hemorrhage may have underpowered the statistical analysis in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Our study also showed that heart failure may also be a predictor of the one-year mortality of patients with cerebral infarction but not of those with cerebral hemorrhage. Previous studies (Eriksson and Olsson 2001;Koton et al 2010) similarly reported that congestive heart failure is a significant predictor of mortality in stroke patients. A small number of heart-failure patients with cerebral hemorrhage may have underpowered the statistical analysis in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Other studies had small sample sizes. 15 Williams and Jiang 24 attempted to develop a To convert glucose to mg/dL, divide by 0.0555. We used χ 2 tests to compare categorical variables and ANOVA or Kruskal-Wallis tests to compare mean and median differences for continuous variables in baseline characteristics.…”
Section: -21mentioning
confidence: 99%
“…Few studies have assessed functional outcome in the longer term, and in particular, longitudinal studies with multiple assessment points are scarce. [8][9][10][11] Stroke recovery is heterogeneous but usually follows a common pattern, in which the largest regain of function occurs during the first weeks poststroke.…”
mentioning
confidence: 99%